Clinical profile and aetiological factors of neonatal jaundice from a rural area of Kutch, Gujarat, India - Patel, Avinash; Saradava, Karan; Chauhan, Hasmukh (International Journal of Contemporary Pediatrics, 2020)
Background: Etiology of hyperbilirubinemia is not only crucial for optimal management of the patient but also it may have implications for subsequent pregnancies. The objective of this study was to study the clinical profile and the underlying aetiological factors leading to neonatal jaundice in this rural setting of Kutch District, Gujarat, India. Methods: This prospective observational study was conducted in the neonatal intensive care unit (NICU) and Post Natal ward Gujarat Adani Institute of Medical Science, Bhuj, Kutch, Gujarat. Total of 150 cases were enrolled for the study. Blood grouping and Rh typing of baby and mother were done. Cord blood bilirubin and haemoglobin, direct coomb's test (DCT) and bilirubin monitoring were done whenever there was a setting for Rh incompatibility. Results: Among 150 neonates studied, majority had birth weight between 2501g and 3000g. Only 21 babies had birth weight <2.5kg (14%) (Table 2). Of the 150 neonates 85 were males and 65 were females. Conclusions: This study concludes that physiological jaundice is the most common cause of neonatal jaundice in our hospital. This is followed by ABO incompatibility, sepsis, Rh incompatibility and idiopathic cases.